Answer:
The required polynomial is f(x)=
![2x^(3)-3x^(2)+3x+7](https://img.qammunity.org/2020/formulas/mathematics/middle-school/rwp15kbptt1r5ky1xuiaay1ww2dpks1viw.png)
Explanation:
Given that polynomial is passing through points (-1,-1) (0,7) ( 1,9) and (2,17)
Let, The required polynomial be f(x)=
![ax^(3)+bx^(2)+cx+d](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8jgkuvw3cfpnfy1we4g5cie6eihi8ssmu5.png)
For point (-1,-1)
f(x)=
![ax^(3)+bx^(2)+cx+d](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8jgkuvw3cfpnfy1we4g5cie6eihi8ssmu5.png)
f(-1)=
![a(-1)^(3)+b(-1)^(2)+c(-1)+d](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jo12oblh65j2js5huza25k31vos77k1q25.png)
(-1)a+b-c+d=(-1) Equation 1
For point (0,7)
f(x)=
![ax^(3)+bx^(2)+cx+d](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8jgkuvw3cfpnfy1we4g5cie6eihi8ssmu5.png)
f(0)=
![a(0)^(3)+b(0)^(2)+c(0)+d](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ajlm8kxhcoh6hjqpkkluwq21o5upni87l1.png)
d=7 Equation 2
For point ( 1,9)
f(x)=
![ax^(3)+bx^(2)+cx+d](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8jgkuvw3cfpnfy1we4g5cie6eihi8ssmu5.png)
f(1)=
![a(1)^(3)+b(1)^(2)+c(1)+d](https://img.qammunity.org/2020/formulas/mathematics/middle-school/d8kohrw1oau4ielv3teivk171x6yew2ztd.png)
a+b+c+d=9 Equation 3
For point (2,17)
f(x)=
![ax^(3)+bx^(2)+cx+d](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8jgkuvw3cfpnfy1we4g5cie6eihi8ssmu5.png)
f(2)=
![a(2)^(3)+b(2)^(2)+c(2)+d](https://img.qammunity.org/2020/formulas/mathematics/middle-school/tn862nk341xfs8b70bfjcihywgfejdbwoz.png)
8a+4b+2c+d=17 Equation 4
Replacing value of d of equation 2 in equation 1,3,4
For equation 1:
(-1)a+b-c+d=(-1)
(-1)a+b-c=(-8)
For equation 3:
a+b+c+d=9
a+b+c=2
For equation 4:
8a+4b+2c+d=17
8a+4b+2c=10
Now,
On adding equation 1 and 3
For equation 1: (-1)a+b-c=(-8)
For equation 3: a+b+c=2
((-1)a+b-c)+(a+b+c)=(-8)+2
2b=(-6)
b=(-3)
Replacing value of b in equation 1 and 4:
For equation 1: (-1)a+b-c=(-8)
(-1)a+(-3)-c=(-8)
(-1)a-c=(-5) Equation 4
For equation 4: 8a+4b+2c=10
8a+4b+2c=10
8a+4(-3)+2c=10
8a+2c=22 Equation 5
For value of a and c:
Equation 4 can be write as
(-1)a-c=(-5)
a+c=5
a=5-c
Replacing value of a in equation 5
8a+2c=22
8(5-c)+2c=22
40-8c+2c=22
-6c=-18
c=3
So,
a=5-c=5-3=2
a=2
Thus,
The value of
a=2, b=(-3), c=3 and d=7
The required polynomial is
f(x)=
![ax^(3)+bx^(2)+cx+d](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8jgkuvw3cfpnfy1we4g5cie6eihi8ssmu5.png)
f(x)=
![2x^(3)-3x^(2)+3x+7](https://img.qammunity.org/2020/formulas/mathematics/middle-school/rwp15kbptt1r5ky1xuiaay1ww2dpks1viw.png)